THE INFLUENCE OF COLLABORATIVE WRITING TECHNIQUE ON STUDENTS’ WRITING SKILLS IN ESSAY - Sutiyono, Akhmad; A., Junaidi (Lentera: Jurnal Ilmiah Kependidikan, 2021)
The present study aimed to investigate the Influence of Collaborative Writing Technie on Students’ Writing Skills in Essay. The objective of this research is to know and describe the influence of Collaborative Writing Technique towards students’ writing skills in Essay. The method of this research was conducted by using quasi experimental method. In collecting the data, the writer used writing test. In analyzing the data, the writer used formula. Based on the result, the writer found that the average score of student’s writing skills on essay in experimental class was higher than control class ( = 67.5 > = 60). Based on the data analysis by using formula that was higher than (3.64 > 2.00 > 2.66). Therefoe, it is concluded that there is an influence of Collaborative Writing Technique towards students’ writing skills in essay at the fifth semester of English Department of STKIP PGRI Bandar Lampung. It means Collaborative Writing Technique is an effective technique which can be implemented by the teacher to improve students’ writing skills, especially in teaching essay.